Dampak Pengalihan Label Halal Terhadap Kinerja dan Kepengurusan Majelis Ulama Indonesia Kabupaten Deli Serdang - Annisa Fitri Siregar; Musaddad Lubis; Dede Pradana; Fitriana Sihaloho; Muhammad Hafiz Hidayatullah; Nazli Badrul Aini Ramdhani (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The issue of halal and haram as a problem that is vulnerable to Muslims in the world, one of which is the State of Indonesia. For the Muslim community in Indonesia, the issue of halal and haram is not just a problem that can be ignored, because this issue is not only about the correlation between fellow human beings, but also the correlation between humans and Allah Ta'ala. Therefore, the issue of the halalness of a product in the form of halal certificates and labels is very crucial for consumers, especially the Muslim community. There are several parties that play a role in the issuance of halal certificates including the Majelis Ulama Indonesia (MUI), BPOM, and also LPPOM MUI. Keywords : halal, haram, MUI, certificates, labels, products